1994
DOI: 10.1037/0097-7403.20.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Trial spacing and trial distribution effects in Pavlovian conditioning: Contributions of a comparator mechanism.

Abstract: A potential basis for trial spacing and trial distribution effects was investigated in rats. In Experiment 1, a conditioned stimulus (e.g., CS A) was trained with either massed (e.g., A---->A---->A) or spaced (e.g., A-->A-->A) trials. When trials were massed, brief exposure to the training context (a condition typical of massed training) impaired responding, whereas more extensive exposure to the context during or after training reduced this apparent massed trials deficit. In Experiment 2, different CSs were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 22 publications
3
31
2
1
Order By: Relevance
“…That any recovery of excitation was observed without further reinforced training with CS-short implies that the low level of excitatory control by CS-short in Experiment 1 and in 2.8 Groups Before-HC and After-HC of Experiment 2 was not mediated by failure of CS-short to enter into excitatory associations with the US. A similar conclusion was recently made by Yin, Barnet, and Miller (1994), who revealed that the detrimental effect of massing all CS-US trials together could be attenuated by posttraining extinction of the conditioning context. This outcome was interpreted to suggest that the deficit in responding to a CS that is massed during training may not reflect a deficit in associative acquisition between the CS and US.…”
Section: Resultssupporting
confidence: 51%
“…That any recovery of excitation was observed without further reinforced training with CS-short implies that the low level of excitatory control by CS-short in Experiment 1 and in 2.8 Groups Before-HC and After-HC of Experiment 2 was not mediated by failure of CS-short to enter into excitatory associations with the US. A similar conclusion was recently made by Yin, Barnet, and Miller (1994), who revealed that the detrimental effect of massing all CS-US trials together could be attenuated by posttraining extinction of the conditioning context. This outcome was interpreted to suggest that the deficit in responding to a CS that is massed during training may not reflect a deficit in associative acquisition between the CS and US.…”
Section: Resultssupporting
confidence: 51%
“…In fact, it is certainly not equivalent in terms of the dynamics of learning and memory (e.g., Roberts, 1974; Adams, 1982; Yin et al, 1994). …”
Section: Resultsmentioning
confidence: 99%
“…With more temporally spaced trials, the associations between the context and the CS and US should be weakened by extinction that occurs during the intertrial interval (for evidence of the context's role in the trial-massing effect, see e.g., Yin et al, 1994). Thus, for an elementally trained CS, the strengths of Links 2 (CScontext) and 3 (context-US) are greater when trials are temporally massed.…”
Section: Trial Massing and Overshadowingmentioning
confidence: 99%